Pilates for rehabilitation - Wood, Samantha 1969- MPT, MBA, PMA-CPT, RYT (Human Kinetics, 2019)
Your patients and athletes demand and deserve customized, adaptable solutions when injury or chronic pain impairs movement and performance. Known for its whole-body approach to fitness, Pilates is the perfect wat to help your patients recover, rehabilitate, and reach their goals. With Pilates for Rehabilitation, you will learn how to apply proven pilates methods to address dysfunction and help your patients achieve optimal performance. Backed by research and proven protocols, author Samantha Wood provides expert advice and detailed exercises for rehabilitating and healing injuries, improving functional strength, promoting efficient movement, and managing pain. Alongside detailed movement instructions using pilates apparatus and mat work, you will learn the indications and contraindications of each exercise and the primary muscles involved so you can determine when the exercise is appropriate for a specific patient. Variations and progressions allow you to adopt exercises based on the stage of rehabilitation or the severity of the injury or condition being treated. Suggested exercise protocols, organized by common orthopedic injuries in anatomical regions, offer you the flexibility to tailor a program to the specific needs of each patient. Pilates for Rehabilitation is the ultimate resource for enhancing stability, mobility, and function in your patients and helping them perform to their full potential